Analisis Normatif Sanksi Bagi Para Pelaku Pencemaran dan Kerusakan Lingkungan Berdasarkan Prespektif Hukum Lingkungan - Efi Sofiah Pajarina (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2023)
Seeing so many cases of pollution and environmental damage that are increasingly more and more complex is one of the problems that must be resolved and addressed immediately. Which based on the analysis conducted at the author of this journal reveals that in order to minimize or even prevent cases of pollution and environmental damage, it is necessary to have a legal instrument that specifically regulates all series of regulations related to environmental management. However, the topic of discussion to be discussed in this journal writing is to emphasize law enforcement for perpetrators of pollution and environmental damage by applying legal sanctions. It should also be underlined that the journal writing method this time uses juridical analysis methods or legal literature studies guided by UUPPLH No. 32 of 2009 as the main foundation. From the results of the analysis that has been carried out, it can be concluded that there are actually 3 types of sanctions that can be given to actors who pollute and damage the environment, including administrative sanctions which include: Reprimand, temporary suspension of operating licenses, revocation of business licenses and the like, then civil sanctions which include: Granting fines, the existence of recovery responsibilities and the like, and the last is criminal sanctions, which include imprisonment, criminal fines, additional penalties and so on. Where these sanctions are given based on how much impact the behavior or actions made by the perpetrators of pollution and damage.